“É um pouquinho de Brasil iaiá”: representações da cidade de Fortaleza na comunicação de marcas de moda no Instagram - Albuquerque, Ticiana Pereira de (2023)
Fashion is presented in this research as a link to the themes of consumption, localism, communication strategies and the neoliberal model, such is the importance of the discipline as a way of understanding society. We analyzed the communication of Ceará authorial fashion brands to identify and categorize the representations of Fortaleza, the state capital. Our corpus includes the brands Ahazando, BABA and Parko. We analyzed their contents posted on Instagram during the period from March 2020 to March 2022. Herring's Web Content Analysis (WebCA) added to exploratory research and conducting semi-structured interviews were the methods that enabled the collection and data analysis. We developed the following categories of analysis: the Scenario City; the Inhabited City, City of Events and the Printed City. Dealing with representations with Hall, fashion with Lipovetsky and Artuso and Simon, localism with Ruschel and Santos, symbolic consumption with Bourdieu and Canclini and alternatives to neoliberalism with Chamayou and Lazaratto, we seek to point out how the brands are presenting Fortaleza and the impact it hás on their positioning. We found that, by using the city as a marketing tool in communication, the brands promoted an exclusive positioning and a high affective appeal, obtaining good results, even in the midst of crises - sanitary and economic - such as the opening of new points of sale, sucessful brand repositioning and national recognition in the media, conducting its strategies with a local bias, valuing its origins, and with the potential to promote new forms of socialization. KEYWORDS: fashion, representation, localism, consumption, Instagram.